Analysis of CDK13-related disorder in a mouse model - Abbad, Aseel (2024)
CDK13-related disorder, a developmental syndrome associated with intellectual disability, facial dysmorphism, congenital heart defects, brain defects, and growth abnormalities, is a recently identified syndrome caused by mutations in the serine-threonine protein kinase CDK13. CDK13 is thought to play roles in transcription regulation and splicing. To date, 135 patients have been identified with a total of 58 variants. The most common variant is c.2525A > G, p.N842S, affecting 45/135 patients. The literature is lacking information on the downstream targets of CDK13 and its role in development.